Costs and length of sepsis-related hospitalizations in Taiwan. Issue 22 (29th May 2020) - Chen, Yen-Jung; Chen, Fu-Lun; Chen, Jin-Hua; Wu, Man-Tzu Marcie; Chien, Du-Shieng; Ko, Yu
Abstract : Abstract: To investigate the healthcare expenditures and length of stay (LOS) of sepsis-related hospitalizations in Taiwan. This is a retrospective claim database study. Data were obtained from the two-million-sample longitudinal health and welfare database (LHWD). Adult patients hospitalized with sepsis between 2010 and 2014 were identified by International Classification of Diseases 9th Edition Clinical Modification (ICD-9-CM) codes, and these patients were divided into three levels of sepsis severity. The amount and distribution of their total medical expenditures were investigated. In total, 62, 517 patients with 97, 790 sepsis-related hospitalizations were included in the present study. It was found that ward fees and medicines comprised the largest component of expenses for sepsis-related hospitalizations. In addition, our study results indicated that the median sepsis-related hospitalization cost was 66.4 thousand New Taiwan Dollar (NT dollars) in 2014, and a significant temporal change was found between 2010 and 2014. The median LOS in a hospital and in an intensive care unit were 11 and 7 days, respectively. Both expenditures and LOS were found to increase with sepsis severity. This study provides an updated and better understanding of the costs and LOS of sepsis-related hospitalizations in Taiwan. It was found that ward fees and medicine fees were the major components of hospital costs. Abstract : Supplemental Digital Content is available in the text